NAQÍL-MAQALLARDA «BALA» KONCEPTI - Djoldasova, S.A. (SCIENCE and SOCIETY, 2025)
This article discusses the concept of child and its significance in proverbs and sayings. It analyzes proverbs and sayings passed down from our ancestors, discusses the role of the concept of child in the family and society, and expresses thoughts from a pedagogical perspective. The issue of folk upbringing was also studied from a religious and spiritual point of view regarding the concept of a child.